2014
DOI: 10.1007/s10803-014-2108-8
|View full text |Cite
|
Sign up to set email alerts
|

The ABC’s of Teaching Social Skills to Adolescents with Autism Spectrum Disorder in the Classroom: The UCLA PEERS ® Program

Abstract: Social skills training is a common treatment method for adolescents with autism spectrum disorder (ASD), yet very few evidence-based interventions exist to improve social skills for high-functioning adolescents on the spectrum, and even fewer studies have examined the effectiveness of teaching social skills in the classroom. This study examines change in social functioning for adolescents with high-functioning ASD following the implementation of a school-based, teacher-facilitated social skills intervention kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 40 publications
4
54
0
1
Order By: Relevance
“…Although the SLCI was retrospective, introducing possible recall bias, the benefits and side effects reported by parents conform well to what is documented in the literature (Troost et al, 2005;Jesner et al 2007;Lemmon et al 2011;McPheeters et al 2011), supporting the validity of parent report for this purpose. Only a minority of parents reported improvements in symptoms related to core features, with decreased rigidity/perseveration being more commonly reported than improved social competency, a finding also supported in reviews of current literature (McPheeters et al 2011).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the SLCI was retrospective, introducing possible recall bias, the benefits and side effects reported by parents conform well to what is documented in the literature (Troost et al, 2005;Jesner et al 2007;Lemmon et al 2011;McPheeters et al 2011), supporting the validity of parent report for this purpose. Only a minority of parents reported improvements in symptoms related to core features, with decreased rigidity/perseveration being more commonly reported than improved social competency, a finding also supported in reviews of current literature (McPheeters et al 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, core symptoms have been reported to improve in other treatment studies using the SRS, which was able to ascertain nuanced incremental changes in response to intervention (Klaiman et al 2013;Laugeson et al 2014). Additional limitations of the study include a relatively small sample size and the likelihood of children's exposure to other interventions while on risperidone.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, social skills training, a common treatment method for adolescents, can be effective for those with high-functioning autism in natural, everyday educational settings. 31 In addition to routine and specialty ASD care, prescription medications may help to stabilize or to manage problem behavior. The data in the present survey on prescription medication use are consistent with results of another study that used EMR data that indicated that stimulants, specifically methylphenidate, are the most commonly prescribed drugs for children with ASD because they target hyperactivity, impulsivity, disinhibition, and inattention.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…El programa PEERS (Programa de Educación y Enriquecimiento de las Habilidades Relacionales) es uno de los más utilizados para trabajar algunos aspectos como la interacción personal, la relación interpersonal, la comunicación social, la A r t í c u l o s respuesta y la motivación social (Chang et al, 2014;Karst et al, 2015;Laugeson, Ellingsen, Sanderson, Tucci & Bates, 2014;Schol et al, 2014;Yoo et al, 2014). Otro de los programas de intervención que se destaca es el Programa de Habilidades Sociales de Superhéroes, el cual trabaja áreas similares a las del programa PEERS, con la diferencia de conseguir el mantenimiento de los resultados a más largo plazo, así como la generalización de los mismos (Block, Radley, Jenson, Clark & O'Neill, 2015;Radley, Jenson, Clark & O'Neill, 2014;Radley, Dart, Moore, Battaglia & LaBrot, 2017).…”
Section: Resultsunclassified